Studi Pengembangan Komponen Implan Paduan Ti6Al4V untuk Aplikasi Biomedis dengan Proses Metal Injection Molding - Dea Anggraheni Pusparasmi; Bambang Suharno; Sugeng Supriadi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Titanium alloy Ti6Al4V is a material that has a combination of mechanical properties required for implants such as good ductility, high corrosion resistance and good biocompatibility, so it is widely used as a material for biomedical implant applications. One method that is currently widely used to produce Ti6Al4V implants is by using the metal injection molding (MIM) process. The MIM process is widely used because it can produce parts more effectively, and low-cost production. One of the important factors in the MIM process is the powder loading of metal powders and the binder system used as feedstock material. So, it is necessary to conduct further studies and in-depth literature review related to this matter. Literature search using the ScienceDirect, a digital database and limited to year 2011-2020. The results of the study show that both the binder and powder loading systems have an influence on the mechanical properties of the injection product, the results are evident that the viscosity of the feedstock decreases with the increase in the shear rate.